Analisis Pengelolaan Program Vokasional Berbasis Kebutuhan Belajar Peserta Didik di Lembaga Pendidikan Kesetaraan Sanggar Kegiatan Belajar (SKB) Kota Surabaya - Siska Agustina; Rivo Nugroho (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Surabaya City Comunity Learning Center has various issues, including a lack of learning materials that include curriculum competencies. The goal of this study was to learn about the management, impediments, and supportive elements of the vocational program at Surabaya City Comunity Learning Center in addressing students' learning needs. This study employs a qualitative technique with descriptive analysis writing. The data validity test is a credibility test that employs source and member triangulation, transferability testing, dependability tests, and confirmability tests. Administrators, students, educators, and educational institutions from the Comunity Learning Center City of Surabaya participated in this study. The study's findings indicate that the Management of Vocational Programs Based on Students' Learning Needs is managed. Based on parts of the management function, such as planning, organizing, implementing, and supervising, that can run smoothly. It has also been running efficiently in the process of managing the vocational program, which is related with attempts to meet the learning demands of pupils. However, there are limitations in the implementation of the vocational program at the Surabaya City Comunity Learning Center in terms of quality sources, infrastructure, and depth of material. This is because Surabaya City Comunity Learning Center is still dependent on partnerships and cannot function independently.